Improving Students’ Speaking Skills Through Social Interaction In The Classroom - Intang, Andi; Latief, Hasnawati; Prabawati Rum, Eka (Journal of Language Testing and Assessment, 2023)
This research purpose to find out improvement of the students’ speaking skills used social interaction at the eighth grade students of SMAN 5 Selayar. The design of this research used a classroom action research which consisted of two cycles. Each cycles consisted of three meetings. The procedure of this research in every cycle consisted of four phases They had plans to action, observation, and reflection Subject matter for the research of class were the pupils XI which consisted of 20 students. The instrument of this research used interview. The result of students speaking skills in terms pronunciation and vocabulary in D-test, cycle I, and cycle II had improved in different scores. The research demonstrated there were was a significant improvement of the students speaking skills used by social interaction models. This statement could prove by the students’ mean score of diagnostic test was 44, but it had increased to 62.6 in cycle I. And in Cycle II was 77.5. it means that the students’ speaking skills from cycle I to cycle II was classified successful. Social Interaction could improve the students’ speaking skills.